LEO VI ARABUS? An Unknown Fragment from the Arabic Translation of Leo VI’s Taktika - Serikoff, Nikolaj (Acta Orientalia Vilnensia, 2003)
The aim of this article is to introduce a hitherto unknown Arabic quotation from the military manual written originally in Greek under the name of the Byzantine Emperor Leo VI (886-912). This quotation is found in the fourteenth century Arabic military treatise At-tadbīrāt as-sulṭānīyya fī siyāsat aṣ-ṣanā’i’ al-ḥtarbīyya written by a Mamlūk high ranking officer, a “colonel” Ibn Mankalī. Greek quotations and longer passages found in military manuals of the Arabs are of great importance. They allow a modern historian to evaluate Byzantine influence on Arab military thought and, moreover, occasionally give some ideas on medieval Arab military intelligence.